2021
DOI: 10.7759/cureus.15604
|View full text |Cite
|
Sign up to set email alerts
|

Electrical Storm With Incessant Ventricular Tachycardia in a COVID-19 Patient: Review of Current Evidence

Abstract: Coronavirus disease 2019 (COVID-19) is associated with various cardiovascular manifestations, including myocarditis, myocardial infarction, and arrhythmias. A prothrombotic state is the primary underlying pathogenic mechanism. While cardiac arrhythmias manifest more commonly amongst critically ill COVID-19 populations, ventricular arrhythmias have been reported only in few cases. This report describes a case of a 95-year-old African American man with COVID-19, who developed sustained monomorphic ventricular ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…An electrical storm is defined as three or more separate episodes of sustained ventricular tachycardia (VT) within 24 h. Sustained VT with hemodynamic instability calls for prompt cardioversion due to it being a state of poor perfusion. Amiodarone may be used both as a preventative measure and for treatment of recurrent monomorphic VT [6]. A recent study showed that polymorphic and irregular ventricular arrhythmias are more common during the active inflammatory phase, whereas monomorphic and regular ventricular arrhythmias are associated with healed myocarditis [7].…”
Section: Myocarditis and Ventricular Tachycardia (Vt)mentioning
confidence: 99%
“…An electrical storm is defined as three or more separate episodes of sustained ventricular tachycardia (VT) within 24 h. Sustained VT with hemodynamic instability calls for prompt cardioversion due to it being a state of poor perfusion. Amiodarone may be used both as a preventative measure and for treatment of recurrent monomorphic VT [6]. A recent study showed that polymorphic and irregular ventricular arrhythmias are more common during the active inflammatory phase, whereas monomorphic and regular ventricular arrhythmias are associated with healed myocarditis [7].…”
Section: Myocarditis and Ventricular Tachycardia (Vt)mentioning
confidence: 99%
“…In COVID-19 patients, ventricular arrhythmias are relatively rare and account for around 6% of inpatient cardiac arrests [250,251], whereas asystole and pulseless electrical activity are more common [252]. Several potential mechanisms may drive ventricular arrhythmias in COVID-19 [253][254][255][256][257]. First, the systemic inflammation may exacerbate pro-arrhythmogenic activity in patients with pre-existing ischaemic cardiomyopathy, myocardial scar and a nidus for ventricular tachycardia (VT) [254].…”
Section: Ventricular Arrhythmiasmentioning
confidence: 99%
“…Second, the COVID-19 inflammatory response can unmask clinically silent nonischaemic cardiomyopathy, leading to VT storm [255]. Third, the COVID-19 infection itself can cause acute myocarditis and/or myocardial injury leading to ventricular arrhythmias [256,257]. There is little evidence supporting the occurrence of ventricular arrhythmias in COVID-19 patients without underlying cardiac disease or myocardial injury [258,259].…”
Section: Ventricular Arrhythmiasmentioning
confidence: 99%